Lessons of the month 3: ST-elevation myocardial infarction and left ventricular thrombus formation: an arterial thrombotic complication of severe COVID-19 infection. Issue 4 (2020) - Fenton, Matthew; Siddavaram, Seshnag; Sugihara, Conn; Husain, Syed
No abstract available